A Web-Based Information System for Monitoring Food Quality in the Free Nutritious Meal Program (MBG): A Case Study of SDN 173 Neglasari, Bandung - PARDEDE, JASMAN; Abdullah, Syadda; Amal M, Ichlasul; Yusuf S, Muhammad; Daffa A R, Muhammad; Ridhwana M, Fadhlan (Integrative Perspectives of Social and Science Journal, 2026)
The implementation of the Free Nutritious Meal Program (MBG) at SDN 173 Neglasari Bandung faces critical operational challenges regarding food safety assurance, where the monitoring mechanism relying on manual methods and verbal communication has proven ineffective. The limitations of this conventional system led to a high risk of losing student complaint information, a slow response time in reporting spoiled food to catering vendors, and a lack of authentic visual evidence, which weakens the school's position in enforcing provider accountability. To address these vulnerabilities, this study designs a web-based monitoring information system using the Rapid Application Development (RAD) approach, focusing on the transformation of manual recording into a digital format. The implementation results demonstrate a tangible impact experienced by users, where teachers can now report incidents with valid visual evidence in under two minutes, eliminating the issue of lost verbal complaints. Meanwhile, the Principal gains direct access to real-time data for objective vendor evaluation. This transformation has proven to significantly enhance complaint handling responsiveness and student nutrition monitoring transparency compared to the previous manual method.